Echoes of Musical Theater and the Image of the Prima Donna in Jean-Jacques Beineix’s «Diva» - Zuiev, Serhii (Scientific herald of Tchaikovsky National Music Academy of Ukraine, 2025)
The relevance of the study. The subject of the intertextual interaction between opera and cinema analyzed in this study is Jean-Jacques Beineix’s film «Diva» (1981). The research explores how operatic codes shape the film’s narrative, visual, and symbolic structures, creating a multilayered cultural text. Four types of the operatic singer’s presence in cinema are identified, including the specific situation in «Diva», where the leading role is performed by opera singer Wilhelmenia Fernandez. Special attention is given to the theme of the voice as a unique phenomenon reconsidered in the context of contemporary artistic issues such as reproduction, replication, simulation, and the quest to preserve authenticity. The film presents numerous allusions to classic opera plots, including Puccini’s «Tosca», Mozart’s «The Magic Flute», Gounod’s «Faust», Verdi’s «Rigoletto», Catalani’s «La Wally», and Wagner’s «Tristan and Isolde». Musical and visual quotations, as well as scenes reminiscent of operatic scenography, are analyzed. The symbolism of motifs such as downfall, sacrifice, and Faustian choice emphasizes the existential dilemmas faced by the characters. The main objective of the study is to reveal the intertextual connections driven by the extensive use of the operatic code in Jean-Jacques Beineix’s film «Diva». The methodology employs an interdisciplinary approach combining semiotic analysis, comparative, and historical-cultural research methods. Using semiotics, Jean-Jacques Beineix’s «Diva» is examined as a text marked by the operatic code, featuring quotations, allusions, and symbols. Comparative analysis and the historical-cultural approach made it possible to trace the constructive interaction between the artistic means of cinema and opera. The phenomenon of the artistic copy functioning in culture is analyzed within the context of postmodernist critical methodology. Results and conclusions. Thus, the director creates the image of an operatic prima donna in the film, correlating it with categories such as high-low, real-unreal, and art-life, placing it within mythological and fantastical contexts while engaging it in extensive intertextual connections. Simultaneously, this image acquires a symbolic dimension where life and art become inseparable. This interaction proves to be productive not only for cinema, which is enriched by established artistic codes, but also for opera, which gains a «fresh» interpretation of well-known plots, a paradoxical «discovery» of the characters’ inner world, and a profound rethinking of musical scores.